Method optimizing DNA extraction on dairy products by real-time PCR targeting porcine-specific mitochondrial DNA gene for halal verification - Rosman, Nurul Natasha; Mustafa, Shuhaimi; Khairil Mokhtar, Nur Fadhilah; Ali, Md. Eaqub (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
Four types of DNA extraction method from commercial dairy products like butter, chocolate and cheese were compared to identify the best DNA yield extractor. Among the four extraction method, the efficiency of CTAB method in extracting DNA was studied in detail with some modification including mechanical lysis, manipulating amount of starting material for DNA extraction and testing different incubation temperature during DNA precipitation. The outcome presented here show that some of this modification have a significant effect on quality and quantity of extracted DNA from the dairy products. This modification allows for significantly higher yield of DNA from processed products than previously reported. The extracted DNA was than further evaluated using real-time PCR assay by targeting mitochondrial (mt) 16S ribosomal RNA (rRNA) gene and positively, all samples was amplifiable by this method. Furthermore, the swine-specific real-time PCR assay also can be performed on commercial samples targeting for 89 base pairs (bp) NADH dehydrogenase subunit 5 (ND5) gene from pork species for identification of pork derivatives in dairy products. These two methods were potentially reliable for food analysis and halal authentication.